In vivo accuracy of dental magnetic resonance imaging in assessing maxillary molar furcation involvement: a feasibility study in humans - Jürchott, Alexander; Sohani, Meysam; Schwindling, Franz Sebastian; Jende, Johann; Kurz, Felix T.; Rammelsberg, Peter; Heiland, Sabine; Bendszus, Martin; Hilgenfeld, Tim (Journal of clinical periodontology, 2020)
Aim To investigate the accuracy and reliability of dental magnetic resonance imaging (dMRI) in assessing maxillary molar furcation involvement (FI). Material and Methods In this prospective study, 22 patients with severe periodontitis underwent cone-beam computed tomography (CBCT) and dMRI. For 192 furcation entrances, the degree of horizontal FI was assessed by two independent observers on both modalities. Results of dMRI were compared with CBCT (reference modality) to assess the accuracy of dMRI. Cohen's kappa (κ), sensitivity and specificity were calculated for FI classification. Bland-Altman analysis and the Kruskal-Wallis test were used to evaluate measurement accuracy of dMRI. Results Based on CBCT findings, 93 furcation entrances revealed FI (degree I/II/III: 35/19/39). Intra- and inter-reader agreement was excellent for both modalities (κ-range: 0.884 to 0.933). dMRI measurements showed high agreement with CBCT (bias: 0.17 mm; 95% limits of agreement: −1.05 to 1.38 mm), and measurement accuracy did not differ among different degrees of FI (p = .67). For FI detection, sensitivity and specificity of dMRI were 98% and 99%. For FI classification, sensitivity values of dMRI were 89%/84%/100% for degree I/II/III. Conclusions Compared to CBCT (non-invasive gold standard), dMRI demonstrates high accuracy and reliability in evaluating the degree of FI in maxillary molars.
First published: 28 April 2020
Gesehen am 05.01.2022